A catered mother's day ebook - Crawford, Isis (A Mystery with Recipes, 2015)
A mom feels taken for granted—but she's got bigger problems when she's taken in for murder: "Engaging...cozy fans will find plenty to like."— Publishers Weekly It's Mother's Day in sleepy Longely, New York, and catering sisters Bernie and Libby Simmons' friend Ellen is an overworked, underappreciated mom who's fed up. She's a dutiful wife and mother while also running her pet-treat business—yet her birthday and anniversary have both been forgotten. But when she tries to fake her own kidnapping as a prank to get back at her family, things go very wrong. The phony ransom note directed her husband to come to a local motel, but when he gets there, Ellen's being arrested for murdering the man whose body is in her room. She insists she doesn't even know him—but her staged abduction doesn't exactly inspire confidence in the police. Now Bernie and Libby will have to cook up a plan to clear their pal's name... Includes original recipes for you to try!